Percepções da Problemática Ambiental pelos Agricultores Familiares do Sudoeste Paraense, Município de Pacajá - Oliveira, Eliene Espírito Santo de; Rocha, Carla Giovana Souza (Sustainability in Debate, 2011)
Inserted study in the carried through actions of research-development in the region of the Transamazônica, Southwest of Pará. The general objective is to identify the decurrent environmental problems of the agricultural activity from the vision of the family farmers. Had been questionnaire used on the practical the 13 families and, 51 on the environmental perceptions. The environmental perceptions add accumulated values, identities and interpretation on the relations and knowledge, conformed in strategies of social reproduction that nor always glimpse the ecological support, but yes material aspects and of exploration of the elements of the natural way for satisfaction them necessities immediate human beings. The ambient question is perceived in the climatic changes to if evidencing drawn out periods of drought and greater heat sensation, and at the same time as concern imposed for the pressure to the attendance to the environmental legislation. The family farmers condition the changes in the practical of “slash-burn” to the support of the governments for implantation of productive alternatives.